Qos improvement evaluation with an effective switch assignment to the controller in real-time sdn environment - Ali, Jehad; Roh, Byeong hee (Software Defined Networks: Architecture and Applications, 2022)
The assignment of switches to the software-defined networking (SDN) controller effect the performance, i.e., end-to-end (E2E) delay in SDN because of frequent communication among the switches in the network and the controllers. The improper allocation of switches to the controller affects the quality-of-service (QoS). Therefore, further investigation is required for the switch assignment process to the SDN controller. In contrast to the previous approaches, in these works, first, we provide an experimental methodology emulated in Mininet to find out the E2E latency between any two nodes in the network with real Internet topologies, and then we partition the network through adopting an effective clustering mechanism to decrease the E2E delay among the switches and the centralized controller. Finally, we compare the results for the E2E delay with the standard K-mean algorithm for the real emulated SDN environment. In this chapter, the controller placement issue is tackled with the allocation of switches to the controllers by calculating the E2E latency in the emulated Mininet environment in the Abilene, Usnet, and OS3E topologies taken from the topology zoo data set using OpenDaylight (ODL) controller.
Keywords: Controller placement problem; Controller placements; End to end; Experimental methodology; Openflow; Performance; Placement problems; Quality-of-service; Real- time; Software-defined networkings; Controller placement problem; OpenFlow; Qualityof-service; Software-defined networking